Adipose Mesenchymal Stem Cell Metabolites Oral Gel Enhance Pro-Angiogenic Factors Expression, Angiogenesis, and Clinical Outcome of Oral Ulcer Rat Model - Wicaksono, Satutya; Nugraha, Alexander Patera; Rahmahani, Jola; Rantam, Fedik Abdul; Kuncorojakti, Suryo; Susilowati, Helen; Riawan, Wibi; Arundina, Ira; Lestari, Pudji; Masya, Resgita Nadila; Surboyo, Meircurius Dwi Condro; Ernawati, Diah Savitri (European Journal of Dentistry, 2023)
Objective Enhancing wound healing capacity is one of the main principles in oral ulcer management. Efficient oral ulcer management will accelerate clinical symptom amelioration and prevent complications. Adipose mesenchymal stem cell metabolites (AdMSCM), a novel biological product, contains a plethora of bioactive mediators that can induce a series of processes in wound healing. This study will analyze the clinical outcome, angiogenesis, and expression of FGF-2 and VEGFA in the oral ulcer rat model after AdMSCM oral gel application.Materials and Methods Twenty healthy male Wistar rats (Rattus novergicus) were used to create oral ulcer animal models. AdMSCM oral gel treatment was performed three times daily for 3 and 7 days. Clinical outcome was assessed by measuring the major diameter of the ulcer; the angiogenesis was evaluated through histological assessment; the expression of VEGFA and FGF-2 was assessed using the immunohistochemistry method.Statistical Analysis This study uses parametric comparative analysis using one-way analysis of variance (ANOVA) and post-hoc Tukey's HSD testResults The application of AdMSCM oral gel in an oral ulcer rat model significantly enhanced the clinical outcome (p < 0.05). In addition, similar results were shown in the histologic assessment of angiogenesis and supported by the significant increase of VEGFA and FGF-2 expression.Conclusions AdMSCM oral gel accelerates oral ulcer healing processes, proven by the enhancement of angiogenesis, pro-angiogenic factors expression, and clinical outcomes.
Keywords: oral ulcer; regenerative medicine; mesenchymal stem cell; dentistry